PENDIDIKAN MULTIKULTURAL MELALUI PENDIDIKAN AGAMA DI SMA NEGERI 2 PURWOKERTO - S Yustiani (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
Implementation of multicultural education at high school levelcould be performed comprehensively through citizenship andreligious educations. SMA 2 Purwokerto has implementedmulticultural education through Islamic education, Christianeducation, and Catholic education. The Subject matters of religiouseducation learning with multicultural perspectives are, for example,tassamuh,fair tolerance, religious functions in community, symbolismand pluralism in religion, Christian democracy, We Love Indonesia,violence and love culture, crediting dialog and collaborating amongreligious people. The teachers apply speech, answer-question, assignment,discussion and study tour methods in multicultural education.Facilities and learning resources in religious education withmulticultural perspectives include class rooms and their facilities,holy Qur 'an, Bible, rosary, musical instruments and Islamic,Christian, and Catholic books.